Organizational Capabilities and University Performance: The Mediating Role of Innovative Academic Programs A Systematic Literature Review - Suci Putri Lestari; Vanessa Gaffar; Lili Adi Wibowo; Alfira Sofia (Dinasti International Journal of Education Management and Social Science, 2026)
This systematic literature review examines the relationships between leadership capability, learning organization, knowledge management strategy, and university performance, with a particular focus on the mediating role of innovative academic programs. The review analyzes 76 peer-reviewed articles published between 2016 and 2025, sourced from Scopus and Web of Science databases. Using the PRISMA 2020 methodology, 17 high-quality studies were identified that directly address the research questions. Data synthesis employed a narrative approach combined with thematic analysis to identify cross-study patterns and convergent findings. Transformational leadership capability significantly influences university performance through innovative academic programs. Learning organization culture and knowledge management strategy demonstrate strong direct and indirect effects on performance outcomes (beta range = 0.38–0.68). Innovative academic programs serve as a crucial partial mediator connecting organizational capabilities with performance outcomes, with partial mediation as the predominant pattern across studies (R2 = 0.58). This review contributes an integrative theoretical framework connecting leadership capability, learning organization, and knowledge management strategy with university performance through innovative academic programs as a mediating mechanism. It advances innovation theory to the higher education context and identifies important boundary conditions and research gaps for future investigation. University leaders should prioritize developing transformational leadership capabilities, cultivating learning organization cultures, implementing comprehensive knowledge management systems, and fostering multi-dimensional academic innovation to achieve superior institutional performance outcomes.